PENGARUH PENYULUHAN HIV/AIDS TERHADAP PENGETAHUAN DAN SIKAP SISWA SMA NEGERI 1 SEPAUK KABUPATEN SINTANG - Elvi Juliansyah; Maretalinia - -; Suyitno - - (VISIKES: Jurnal Kesehatan Masyarakat, 2020)
HIV (Human Immunodeficiency Virus) was a virus that attacks the human immune system that can cause AIDS (Acquired Immuno Deficiency Syndrome). AIDS was a collection of symptoms that arise from a decrease in the immune system. The aim of this study was to determine differences between knowledge and attitudes of Senior High School Number 1 Sepauk students before and after HIV / AIDS counselling. The research’s method used was a quantitative method with the design of One Group Pre-test Post-test conducted the first observation (pre-test) that allows testing the changes that occur after the experiment (program). The research sample was taken using a convenience sample technique of 40 students. The results showed that HIV / AIDS counselling could improve students' knowledge of 2.9, namely from 90.28 (before HIV / AIDS counselling was conducted) changed to 93.18. T-test results obtained p value = 0.022 meaning that statistically there were significant differences in knowledge before and after HIV / AIDS counselling. HIV / AIDS counselling can improve students' attitudes 1.57, from 92.25 (before HIV / AIDS counselling) changes to 93.82 (after HIV / AIDS counselling). It could be concluded that counselling need to be conducted continuously to students to improve knowledge and change the attitudes of high school students 1 Sepauk Sintang Regency.Keywords: Counselling, HIV / AIDS, Knowledge, Attitudes, and Students.